Continuance [compact disc] - Alexander, Joey (Mack Avenue, 2023)
Pianist/composer Joey Alexander's seventh album is the story of a critically acclaimed artist at the peak of his creativity, not only as a bandleader but as a celebrated composer. At twenty-years-old, Alexander has gathered his touring band consisting of Kris Funn (bass) and John Davis (drums) to translate their unique improvisation on the stage to the studio with the help of trumpeter Theo Croker.